Glass compositions, fiberizable glass compositions, and glass fibers made therefrom

JP2025036447APending Publication Date: 2025-03-14ELECTRIC GLASS FIBER AMERICA LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024216993
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-03-07
Filing Date
2024-12-11
Publication Date
2025-03-14

Smart Images

  • Figure 2025036447000001
    Figure 2025036447000001
  • Figure 2025036447000002
    Figure 2025036447000002
  • Figure 2025036447000003
    Figure 2025036447000003
Patent Text Reader

Abstract

To provide glass compositions.SOLUTION: Glass compositions suitable for fiber forming having low levels of Li2O and glass fibers having high elastic modulus are disclosed. The glass composition may include about 59-about 63 wt.% of SiO2, about 13.7-about 16 wt.% of Al2O3, about 14-about 16.5 wt.% of CaO, about 6-about 8.5 wt.% of MgO, less than 1 wt.% of Fe2O3 and less than 1 wt.% of TiO2. In some cases, the composition may be substantially free of Li2O. In some cases, the composition may include Li2O up to 0.5 wt.%. In some cases, RE2O3 may be present in the composition in an amount up to 1.5 wt.%. The glass compositions can be used to form glass fibers which can be incorporated into a variety of other fiber glass products (e.g., strands, rovings, fabrics, etc.) and incorporated into various composites.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Priority This application claims the benefit of and priority to U.S. Provisional Patent Application No. 62 / 639,731, filed March 7, 2018, which is incorporated by reference in its entirety as if fully set forth herein.

[0002] Field Described herein are glass compositions, particularly glass compositions for forming fibers. [Background technology]

[0003] background Glass fibers have been used for many years to reinforce various polymer resins. Some commonly used glass compositions for use in reinforcement applications include the "E-glass", "R-glass" and "D-glass" families of compositions. "S-glass" is another commonly used family of glass compositions and includes, for example, glass fibers commercially available from AGY (Aiken, South Carolina) under the trademark "S-2 Glass".

[0004] Glass fibers are divided into two categories: general purpose and specialty. The most widely used glass fiber type is the general purpose type, also known as E-glass fiber. E-glass exhibits good overall mechanical, electrical and corrosion properties.

[0005] As the viable market applications for composites continue to grow, fiberglass users have been challenged to meet demands for performance, cost, reliability and durability, as well as an increased focus on sustainability and environmental stewardship. Such challenges include ever-increasing wind blade length requirements, power generation equipment seeking to maximize pipe and tank performance and life in harsh conditions and environments, the demand for fuel economy at the expense of performance is driving changes in the automotive industry, and continuing technological advances requiring ever more robust circuit board signal speeds. Summary of the Invention [Problem to be solved by the invention]

[0006] Fiberglass manufacturers continue to seek glass compositions that can be used to form glass fibers having desirable mechanical properties in a commercial manufacturing environment. [Means for solving the problem]

[0007] Abstract Various embodiments of the present invention provide glass compositions, fiberizable glass compositions, and glass fibers formed from such compositions, as well as fiberglass strands, yarns, fabrics, and composites including such glass fibers, adapted for use in a variety of applications.

[0008] In one embodiment, a glass composition suitable for fiber formation has about 60 to about 63 weight percent SiO, about 14 to about 16 weight percent AlO, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, and less than 1 weight percent FeO. , and less than 1 weight percent TiO2, is substantially free of Li2O, and has a (Li2O+MgO+Al2O3) content ranging from about 22 to 24 weight percent.

[0009] In one particular embodiment, a glass composition suitable for fiber formation can include about 60 to about 63 weight percent SiO, about 14 to about 16 weight percent AlO, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, and rare earth oxides REO in an amount greater than 0 weight percent and less than 1 weight percent, and is substantially free of LiO.

[0010] In certain embodiments, a glass composition suitable for fiber formation can include about 59 to about 63 weight percent SiO, about 13.7 to about 16 weight percent AlO, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, and rare earth oxides REO in an amount greater than 0 weight percent and less than 1.5 weight percent, and is substantially free of LiO.

[0011] In some cases, a glass composition suitable for fiber formation can include about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, less than 1 weight percent TiO2, less than 0.5 weight percent Li2O, with RE2O3 present in an amount greater than 0 weight percent and less than 1 weight percent, and the (Li2O+MgO+Al2O3) content ranging from about 22 to 24 weight percent.

[0012] In some embodiments, a glass composition suitable for fiber formation can include about 60 to about 63 weight percent SiO, about 14 to about 16 weight percent AlO, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, LiO is present in an amount greater than 0 weight percent and less than 0.5 weight percent, and the (LiO+MgO+AlO) content ranges up to about 22-23 weight percent.

[0013] In any of the preceding embodiments, additional embodiments may include an Al2O3 / (Al2O3+MgO+CaO) ratio in the range of 0.33 to 0.47. In certain embodiments, the Al2O3 / (Al2O3+MgO+CaO) ratio may be less than 0.40. In some embodiments, the Al2O3 / (Al2O3+MgO+CaO) ratio may be in the range of 0.37 to 0.42. In some embodiments, the Al2O3 / (Al2O3+MgO+CaO) ratio may be in the range of 0.35 to 0.45.

[0014] Some embodiments of the present invention relate to fiberglass strands. Several fiberizable glass compositions are disclosed herein as part of the present invention, and it should be understood that various embodiments of the present invention may include glass fibers, fiberglass strands, yarns, and other products incorporating glass fibers formed from such compositions. In one embodiment, a plurality of glass fibers formed from a glass composition may include about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, less than 1 weight percent TiO2, Li2O is present in an amount greater than 0 weight percent and less than 0.5 weight percent, the (Li2O+MgO+Al2O3) content ranges from about 22 to 24 weight percent, and the Young's modulus is greater than 85 GPa.

[0015] Some embodiments of the present invention relate to yarns formed from at least one fiberglass strand formed from the glass compositions described herein. Some embodiments of the present invention relate to fabrics incorporating at least one fiberglass strand formed from the glass compositions described herein. In some embodiments, the weft yarns used in the fabric can include at least one fiberglass strand. The warp yarns can include at least one fiberglass strand in some embodiments. In some embodiments, fiberglass strands can be used in both the weft and warp yarns to form fabrics according to the present invention. In some embodiments, the fabrics of the present invention can include plain weave, twill, crowfoot fabric, satin weave, stitchbond fabric, or 3D woven fabric.

[0016] Some embodiments of the present invention relate to a composite material comprising glass fibers formed from a polymeric resin and one of the various glass compositions described herein. The glass fibers can be obtained from fiberglass strands according to some embodiments of the present invention. In some embodiments, the glass fibers can be incorporated into a fabric, such as a woven fabric. For example, the glass fibers can be present in the weft and / or warp yarns that are woven to form the fabric. In embodiments in which the composite material comprises a fabric, the fabric can include a plain weave, a twill, a houndstooth weave, a satin weave, a stitch-bonded fabric, or a 3D woven fabric.

[0017] Glass fibers can be incorporated into other forms of composites, which are discussed in more detail below.

[0018] The composites of the present invention can include one or more of a variety of polymeric resins. In some embodiments, the polymeric resin can include at least one of polyethylene, polypropylene, polyamide, polyimide, polybutylene terephthalate, polycarbonate, thermoplastic polyurethane, phenolic resin, polyester, vinyl ester, polydicyclopentadiene, polyphenylene sulfide, polyether ether ketone, cyanate ester, bis-maleimide, and thermosetting polyurethane resin. In some embodiments, the polymeric resin can include an epoxy resin.

[0019] The composites of the present invention may be in a variety of forms and used in a variety of applications. Some examples of potential uses for composites according to some embodiments of the present invention include, but are not limited to, wind energy (e.g., wind turbine blades), automotive applications, safety / security applications (e.g., bulletproof armor), aerospace or aviation applications (e.g., airplane interior floors), high pressure vessels or tanks, missile casings, electronic devices, etc.

[0020] These and other embodiments of the invention are described in more detail in the detailed description that follows. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Detailed Description of the Invention The present embodiments generally relate to glass compositions. In one aspect, the present invention provides glass fibers formed from the glass compositions described herein. Specifically, the glass compositions described herein may be free of Li2O. Optionally, the compositions may include small amounts of lithium oxide (Li2O). In some cases, the glass compositions may include one or more rare earth oxides (RE2O3). In some embodiments, the glass fibers of the present invention may have improved mechanical properties, such as Young's modulus, as compared to conventional E-glass fibers, for example. In some embodiments, the glass fibers may have an elastic modulus of greater than 85 GPa. In certain embodiments, the glass fibers may have an elastic modulus of greater than 88 GPa. In some embodiments, the glass fibers may have an elastic modulus of greater than 2.7 g / cm 3 In one particular embodiment, the glass fibers can have a forming temperature (T F In some embodiments, the glass fibers may have a liquidus temperature (T L In some embodiments of the glass composition, T F and T F ("Delta T") may be greater than about 60°C. In certain embodiments, the glass composition has a melting temperature (T M ). Definitions and Explanations

[0022] The terms "invention," "the invention," "the present invention," "embodiment," "certain embodiment," and the like, as used herein, are intended to broadly refer to all subject matter of this application and the claims that follow. Statements containing these terms should not be understood to limit the meaning or scope of the subject matter described herein or the claims of the present invention that follow. The terms "comprising," "having," "including," and "containing" are used interchangeably herein unless otherwise noted. The term "a," "an ... Please note that "an" and "the" include multiple referents unless clearly and unambiguously limited to one referent.

[0023] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. However, any numerical value inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements. Moreover, any range disclosed herein should be understood to encompass any and all subranges contained within that range. For example, a range defined as "1-10" should be considered to include any and all subranges between a minimum value of 1 and a maximum value of 10 (inclusive), i.e., all subranges beginning with a minimum value of 1 or greater, e.g., 1-6.1, and ending with a maximum value of 10 or less, e.g., 5.5-10. Moreover, any reference referred to as "incorporated herein" should be understood to be incorporated in its entirety.

[0024] The glass compositions are described in terms of weight percentage (wt.%) based on the total weight of the composition. Glass compositions and fibers

[0025] The present invention can be embodied in various ways. In some embodiments, a glass composition suitable for fiber formation can include SiO2, Al2O3, CaO, MgO, Fe2O3, and TiO2. Optionally, the composition can further include RE2O3. Optionally, the composition can further include Li2O. In some embodiments, the composition can be substantially free of Li2O.

[0026] In certain embodiments, glass compositions suitable for fiber formation as described herein can include about 59 to about 63 weight percent (e.g., 60 wt.% to 63 wt.%) SiO2. For example, the composition can include about 59 wt.%, about 59.1 wt.%, about 59.2 wt.%, about 59.3 wt.%, about 59.4 wt.%, about 59.5 wt.%, about 59.6 wt.%, about 59.7 wt.%, about 59.8 wt.%, about 59.9 wt.%, about 60 wt.%, about 60.1 wt.%, about 60.2 wt.%, about 60.3 wt.%, about 60.4 wt.%, about 60.5 wt.%, about 60.6 wt.%, about 60.7 wt.%, about 60.8 wt.%, about 60.9 wt.%, about 60.1 wt.%, about 60.2 wt.%, about 60.4 wt.%, about 60.5 wt.%, about 60.6 wt.%, about 60.7 wt.%, about 60.8 wt.%, about 60.9 wt.%, about 60.8 wt.%, about 60.9 wt.%, about 60.9 wt.%, about 60.1 wt.%, about 60.2 wt.%, about 60.4 wt.%, about 60.5 wt.%, about 60.6 wt.%, about 60.7 wt.%, about 60.8 wt.%, about 60.9 ... Approx. 60.3wt.%, approx. 60.4wt.%, approx. 60.5wt.%, approx. 60.6wt.%, approx. 60.7wt.%, approx. 60.8wt.%, approx. 60.9wt. %, approx. 61wt.%, approx. 61.1wt.%, approx. 61.2wt.%, approx. 61.3wt.%, approx. 61.4wt.%, approx. 61.5wt.%, approx. 61.6wt. %, about 61.7 wt.%, about 61.8 wt.%, about 61.9 wt.%, about 62 wt.%, about 62.1 wt.%, about 62.2 wt.%, about 62.3 wt.%, about 62.4 wt.%, about 62.5 wt.%, about 62.6 wt.%, about 62.7 wt.%, about 62.8 wt.%, about 62.9 wt.%, or about 63 wt.% SiO2.

[0027] In some examples, glass compositions suitable for fiber formation as described herein can include about 13.7 to about 16.5 weight percent (e.g., 14 wt.% to 16 wt.%) Al2O3. For example, compositions can include about 13.7, about 13.8, about 13.9, about 14 wt.%, about 14.1 wt.%, about 14.2 wt.%, about 14.3 wt.%, about 14.4 wt.%, about 14.5 wt.%, about 14.6 wt.%, about 14.7 wt.%, about 14.8 wt.%, about 14.9 wt.%, about 15 wt.%, about 15.1 wt.%, about 15.2 wt.%, about 15.3 wt.%, about 15.4 wt.%, about 15.5 wt.% Al2O3. It may include Al2O3 in an amount of about 15.6 wt.%, about 15.7 wt.%, about 15.8 wt.%, about 15.9 wt.%, about 16 wt.%, about 16.1 wt.%, about 16.2 wt.%, about 16.3 wt.%, about 16.4 wt.%, or about 16.5 wt.%.

[0028] In some embodiments, glass compositions suitable for fiber formation as described herein can include about 14 to about 16.5 weight percent (e.g., 14 wt.% to 16 wt.%) CaO. For example, the compositions can include about 14 wt.%, about 14.1 wt.%, about 14.2 wt.%, about 14.3 wt.%, about 14.4 wt.%, about 14.5 wt.%, about 14.6 wt.%, about 14.7 wt.%, about 14.8 wt.%, about 14.9 wt.%, about 15 wt.%, about 15.1 wt.%, about 15.2 wt.%, about 15.3 wt.%, about 15.4 wt.%, about 15.5 wt.% CaO. It may contain CaO in an amount of about 15.6 wt.%, about 15.7 wt.%, about 15.8 wt.%, about 15.9 wt.%, about 16 wt.%, about 16.1 wt.%, about 16.2 wt.%, about 16.2 wt.%, about 16.4 wt.%, or about 16.5 wt.%.

[0029] In some embodiments, glass compositions suitable for fiber formation as described herein can include about 6 to about 8.5 weight percent (e.g., 6 wt.% to 8 wt.%) MgO. For example, the composition can include MgO in an amount of about 6 wt.%, about 6.1 wt.%, about 6.2 wt.%, about 6.3 wt.%, about 6.4 wt.%, about 6.5 wt.%, about 6.6 wt.%, about 6.7 wt.%, about 6.8 wt.%, about 6.9 wt.%, about 7 wt.%, about 7.1 wt.%, about 7.2 wt.%, about 7.3 wt.%, about 7.4 wt.%, about 7.5 wt.%, about 7.6 wt.%, about 7.7 wt.%, about 7.8 wt.%, about 7.9 wt.%, about 8 wt.%, about 8.1 wt.%, about 8.2 wt.%, about 8.3 wt.%, about 8.4 wt.%, or about 8.5 wt.%.

[0030] In some embodiments, glass compositions suitable for fiber formation as described herein may include Fe2O3 in an amount less than 1 weight percent. For example, the composition may include Fe2O3 in an amount of about 0.25 wt.%, about 0.3 wt.%, about 0.35 wt.%, about 0.4 wt.%, about 0.45 wt.%, about 0.5 wt.%, about 0.55 wt.%, about 0.6 wt.%, about 0.65 wt.%, about 0.7 wt.%, about 0.75 wt.%, about 0.8 wt.%, about 0.85 wt.%, about 0.9 wt.%, about 0.95 wt.%, or up to about 1.0 wt.%. In some cases, the composition may be substantially free of Fe2O3.

[0031] In some embodiments, glass compositions suitable for fiber formation as described herein may include TiO2 in an amount less than 1 weight percent. For example, the composition may include about 0.25 wt.%, about 0.3 wt.%, about 0.35 wt.%, about 0.4 wt.%, about 0.45 wt.%, about 0.5 wt.%, about 0.55 wt.%, about 0.6 wt.%, about 0.65 wt.% , about 0.7 wt.%, about 0.75 wt.%, about 0.8 wt.%, about 0.85 wt.%, about 0.9 wt.%, about 0.95 wt.%, or about 1.0 wt.% TiO2. In some cases, the composition may be substantially free of TiO2.

[0032] Optionally, some embodiments of glass compositions suitable for fiber formation as described herein can include Li2O in an amount of less than 0.5 weight percent (e.g., less than 0.4 wt.%). For example, the composition can include Li2O in an amount of about 0.05 wt.%, about 0.1 wt.%, about 0.15 wt.%, about 0.2 wt.%, about 0.25 wt.%, about 0.3 wt.%, about 0.35 wt.%, about 0.4 wt.%, about 0.45 wt.%, or about 0.5 wt.%. In some cases, the composition can be substantially free of Li2O.

[0033] Optionally, some embodiments of glass compositions suitable for fiber formation as described herein can include rare earth oxides ("RE2O3") in an amount less than 1 weight percent. In some embodiments, the glass compositions can include RE2O3 in an amount less than 1.5 weight percent. For example, the composition can include RE2O3 in an amount of up to about 0.2 wt.%, about 0.25 wt.%, about 0.3 wt.%, about 0.35 wt.%, about 0.4 wt.%, about 0.45 wt.%, about 0.5 wt.%, about 0.55 wt.%, about 0.6 wt.%, about 0.65 wt.%, about 0.7 wt.%, about 0.75 wt.%, about 0.8 wt.%, about 0.85 wt.%, about 0.9 wt.%, about 0.95 wt.%, about 1.0 wt.%, about 1.1 wt.%, about 1.2 wt.%, about 1.3 wt.%, about 1.4 wt.%, or about 1.5 wt.%. As used herein, the term "rare earth oxide" refers to oxides incorporating rare earth metals, as would be understood by one of ordinary skill in the art, including oxides of the following metals; scandium (Sc2O3), yttrium (YO3), and the lanthanide elements (lanthanum (La2O3), cerium (Ce2O3 and CeO2), praseodymium (Pr2O3), neodymium (Nd2O3), promethium (Pm2O3), samarium (Sm2O3), europium (Eu2O3 and EuO), gadolinium (Gd2O3), terbium (Tb2O3), dysprosium (Dy2O3), holmium (Ho2O3), erbium (Er2O3), thulium (Tm2O3), ytterbium (Yb2O3), and lutetium (Lu2O3). The rare earth oxides may be included in the glass compositions of the present invention in amounts greater than those present only as contaminants or impurities in batch materials included with the glass batch to provide another component. The glass compositions may, in some embodiments, include combinations of rare earth oxides (e.g., one or more of various rare earth oxides). In some embodiments, RE2O3 may include at least one of La2O3, YO3, Sc2O3, and Nd2O3. In some embodiments, RE2O3 may be YO3. In some embodiments, the YO3 content may be about 1 weight percent or less.In some cases, RE2O3 can be present in an amount greater than 0 weight percent and less than 1.5 weight percent. In some cases, the composition can be substantially free of RE2O3.

[0034] Without wishing to be bound by theory, the inclusion of Y2O3 in the glass composition can favorably affect the glass softening temperature and glass transition temperature, as well as the elastic modulus, tensile strength, elongation, coefficient of thermal expansion, and other properties of glass fibers formed from the composition.

[0035] In some embodiments, glass compositions suitable for fiber formation as described herein may include up to about 22-23 weight percent (Li2O+MgO+Al2O3). In some embodiments, glass compositions suitable for fiber formation may include up to about 22-24 weight percent (Li2O+MgO+Al2O3). For example, compositions may include up to about 22 wt.%, about 22.1.1 wt.%, about 22.2 wt.%, about 22.3 wt.%, about 22.4 wt.%, about 22.5 wt.%, about 22.6 wt.%, about 22.7 wt.%, about 22.8 wt.%, about 22.9 wt.%, about 2 ... 2.4 wt.%, about 22.5 wt.%, about 22.6 wt.%, about 22.7 wt.%, about 22.8 wt.%, about 22.9 wt.%, about 23 wt.%, about 23.1 wt.%, about 23.2 wt.%, about 23.3 wt.%, about 23.4 wt.%, about 23.5 wt.%, about 23.6 wt.%, about 23.7 wt.%, about 23.8 wt.%, about 23.9 wt.%, or about 24 wt.% (LiO+MgO+AlO).

[0036] In some embodiments, glass compositions suitable for fiber formation as described herein can include a ratio of CaO to MgO ("CaO / MgO") from about 1.6 to about 2.8 (e.g., 1.7 to 2.0). For example, the composition can include an amount of CaO / MgO of about 1.6, about 1.65, about 1.7, about 1.75, about 1.8, about 1.85, about 1.9, about 1.95, about 2.0, about 2.15, about 2.2, about 2.25, about 2.3, about 2.35, about 2.4, about 2.45, about 2.5, about 2.55, about 2.6, about 2.65, about 2.7, about 2.75, or about 2.8.

[0037] In some embodiments, glass compositions suitable for fiber formation as described herein can include a ratio of SiO2 to Al2O3 ("SiO2 / Al2O3") from about 3.5 to about 4.6 (e.g., from about 3.9 to about 4.3, from about 4 to about 4.5, from greater than 4 to 4.5). For example, the composition can include an amount of SiO2 / Al2O3 of about 3.5, about 3.55, about 3.6, about 3.65, about 3.7, about 3.75, about 3.8, about 3.85, about 3.9, about 3.95, about 4, about 4.05, about 4.1, about 4.15, about 4.2, about 4.25, about 4.3, about 4.35, about 4.4, about 4.45, about 4.5, about 4.55, or about 4.6. In some embodiments, SiO2 / Al2O3 can be greater than 4.

[0038] In some embodiments, glass compositions suitable for fiber formation as described herein can include a ratio of Al2O3 to (Al2O3+CaO+MgO) ("Al2O3 / (Al2O3+CaO+MgO)") from about 0.33 to about 0.47 (e.g., from about 0.35 to about 0.41, less than about 0.35 to 0.40). For example, the composition can include Al2O3 / (Al2O3+CaO+MgO) in an amount of about 0.33, about 0.34, about 0.35, about 0.36, about 0.37, about 0.38, about 0.39, about 0.40, about 0.41, about 0.42, about 0.43, about 0.44, about 0.45, about 0.46, or about 0.47. In some embodiments, Al2O3 / (Al2O3+CaO+MgO) can be less than 0.40. In other embodiments, the Al2O3 / (Al2O3+MgO+CaO) ratio may range from 0.37 to 0.42.

[0039] In some embodiments, the glass composition may include up to 0.2 weight percent Na2O. In some cases, the composition may be substantially free of Na2O. In certain embodiments, the glass composition may include up to 0.2 weight percent K2O. In some cases, the composition may be substantially free of K2O. In some embodiments, the glass composition may be substantially free of at least one of Zn, F, B, or Sr.

[0040] In some embodiments, glass compositions suitable for fiber formation can include about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some embodiments, the (Li2O+MgO+Al2O3) content can range up to about 22 to 24 weight percent.

[0041] In some cases, the glass composition suitable for fiber formation is about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, less than 1 weight percent TiO2, and RE2O3 present in an amount greater than 0 weight percent and less than 1 weight percent. In some embodiments, the composition may be substantially free of Li2O.

[0042] In certain embodiments, a glass composition suitable for fiber formation can include about 59 to about 63 weight percent SiO, about 13.7 to about 16 weight percent AlO, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, and rare earth oxides REO in an amount greater than 0 weight percent and less than 1.5 weight percent, and is substantially free of LiO.

[0043] In certain embodiments, a glass composition suitable for fiber formation can include about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, less than 1 weight percent TiO2, less than 0.5 weight percent Li2O, and RE2O3 present in an amount greater than 0 weight percent and less than 1 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content can range up to about 22 to 24 weight percent.

[0044] In some embodiments, glass compositions suitable for fiber formation can include about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, less than 1 weight percent TiO2, and Li2O present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content ranges up to about 22 to 23 weight percent.

[0045] It should be understood that any component of the glass composition described as being present in an amount between about 0 weight percent and another weight percent is not necessarily required in all embodiments. Such components may be optional in some embodiments. Similarly, in some embodiments, the glass composition may be substantially free of some components, and any amount of a component present in the glass composition may result from a component present as a trace impurity in the batch materials. A component present as a trace impurity may not be intentionally added to the glass composition, but may be present in the glass compositions described herein because it is present as an impurity in a starting material added to the glass composition. Generally, trace impurities are present in the glass composition in an amount of about 0.1 weight percent or less, although some trace impurities may be present in the glass composition in an amount up to about 0.5 weight percent.

[0046] In some embodiments, the glass compositions of the present invention may be fiberizable. In some embodiments, the glass compositions may have a forming temperature (T F As used herein, the term "formation temperature" or T F means the temperature (or "log3 temperature") at which the glass composition has a viscosity of 1000 poise. In some embodiments, the glass composition has a forming temperature (T F ) can be used. For example, T F may be rounded to the nearest 5°C to about 1200°C, about 1205°C, about 1210°C, about 1215°C, about 1220°C, about 1225°C, about 1230°C, about 1235°C, about 1240°C, about 1245°C, about 1250°C, about 1255°C, about 1260°C, about 1265°C, about 1270°C, about 1275°C, about 1280°C, about 1285°C, about 1290°C, about 1295°C, about 1300°C, about 1305°C, about 1310°C, about 1315°C, about 1320°C, about 1325°C, about 1330°C, about 1335°C, about 1340°C, about 1345°C, or about 1350°C. .

[0047] In some embodiments, the glass composition has a liquidus temperature (T L ) can be used. For example, T L may be rounded to the nearest 5°C to about 1120°C, about 1125°C, about 1130°C, about 1135°C, about 1140°C, about 1145°C, about 1150°C, about 1155°C, about 1160°C, about 1165°C, about 1170°C, about 1175°C, about 1180°C, about 1185°C, about 1190°C, about 1195°C, about 1200°C, about 1205°C, about 1210°C, about 1215°C, about 1220°C, about 1225°C, about 1230°C, about 1235°C, about 1240°C, about 1245°C, or about 1250°C.

[0048] In some embodiments, the forming temperature of the glass composition (T F ) and liquidus temperature (T L) may be desirable for commercial fiberglass manufacturing operations. For example, in some embodiments of the glass composition, T F and T F ("delta T") may be greater than about 60°C (e.g., greater than 80°C, greater than 100°C). For example, delta T may be about 62°C, about 64°C, about 66°C, about 68°C, about 70°C, about 72°C, about 74°C, about 76°C, about 78°C, about 80°C, about 82°C, about 84°C, about 86°C, about 88°C, about 90°C, about 92°C, about 94°C, about 96°C, about 98°C, about 100°C, about 105°C, about 110°C, about 115°C, or about 120°C.

[0049] In some embodiments, the glass composition has a melting temperature (T M ) can be used. For example, T M may be about 1465°C, about 1468°C, about 1470°C, about 1472°C, about 1474°C, about 1476°C, about 1478°C, about 1480°C, about 1482°C, about 1484°C, about 1486°C, about 1488°C, about 1490°C, about 1492°C, about 1494°C, about 1496°C, about 1498°C, about 1500°C, about 1502°C, about 1504°C, about 1506°C, about 1508°C, about 1510°C, about 1512°C, about 1514°C, about 1516°C, about 1518°C, about 1520°C, about 1522°C, about 1524°C, about 1526°C, about 1528°C, or about 1530°C.

[0050] In some embodiments, the glass fibers can be formed from the glass compositions described herein. If desired, the glass fibers can be arranged into a fabric. In some embodiments, the glass fibers can be provided in other forms, including, for example and not limited to, continuous strands, chopped strands (dry or wet), yarns, rovings, prepregs, and the like. Various embodiments of the glass compositions (and any fibers formed therefrom) can be used in a variety of applications. In some embodiments, the fibers can be fiberglass strands, and in other embodiments, yarns including fiberglass strands. Some embodiments of the yarns may be particularly suitable for textile applications. In some embodiments, the fibers can be fiberglass cloth. Some embodiments of the fiberglass cloth of the present invention are particularly suitable for use in reinforcement applications, especially where high modulus, high strength, and / or high elongation are important.

[0051] Some embodiments of the present invention may relate to composites incorporating fiberglass strands, fiberglass yarns, and fiberglass fabrics, such as fiber reinforced polymer composites. Some composites may be particularly suitable for use in reinforcement applications, particularly where high modulus, high strength, and / or high elongation are important, such as wind energy (e.g., wind turbine blades), automotive applications, safety / security applications (e.g., bulletproof armor or armor panels), aerospace or aviation applications (e.g., airplane interior floors), high pressure vessels or tanks, missile casings, and the like.

[0052] Some embodiments of the present invention relate to composites suitable for use in wind energy applications. The composites of the present invention are suitable for wind turbine blades, particularly as compared to other long wind turbine blades. The composite material may be suitable for use in longer wind turbine blades that are lighter yet stronger. Lighter weight and greater stability of wind energy blades are very important considerations for the selection of composite materials. Wind energy blade design has changed over time to pursue longer blades to capture more energy. Some blades are 82 meters long and can benefit from improved fiber composites. Stronger fiberglass composites, such as those disclosed herein, may be useful to achieve larger wind blade sizes while providing the strength and weight required to stay within the load design of the wind turbine. Lighter and stronger materials, such as those of the present invention, can increase energy yield, improve operating costs, reduce installation costs, ease of transportation, and improve safety.

[0053] Still other embodiments of the present invention may relate to automotive composites. Some embodiments of the present invention may relate to aerospace composites. Other embodiments of the present application may relate to aviation composites. Some embodiments of the present invention may relate to composites for safety / security applications, such as armor panels. Other embodiments of the present invention may relate to composites for high pressure vessels or storage tanks. Some embodiments of the present invention may relate to composites for missile casings. Other embodiments of the present invention may relate to composites for use in high temperature insulation applications. Some embodiments of the present invention may relate to printed circuit boards, such as substrates for chip packaging, where a lower coefficient of thermal expansion is particularly desirable. Some embodiments of the present invention may relate to prepregs. Some embodiments of the present invention may relate to long fiber reinforced thermoplastics (LFTs) for various automotive parts. Some embodiments of the present invention may relate to pipes or tanks for chemical transport and storage. Some embodiments of the present invention may relate to non-woven textured fibers for thermal and acoustic management applications, such as mufflers for motorcycles, cars, and trucks. Some embodiments of the present invention may relate to electrical insulation rods or cables. Some embodiments of the present invention may relate to composite rebar to replace steel rebar for road infrastructure, bridges, and buildings.

[0054] Some embodiments of the present invention relate to fiber glass strands. In some embodiments, the fiber glass strands of the present invention include a plurality of glass fibers. In some embodiments, the plurality of glass fibers can be formed from a glass composition including about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition can range from about 22 to 24 weight percent. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition can range from about 1.7 to about 2.0. In some embodiments, the composition can be substantially free of F2. In some embodiments, the composition can further include up to 0.2 weight percent Na2O. Optionally, the composition may further comprise up to 0.2 weight percent KO.

[0055] In some embodiments, the plurality of glass fibers may be formed from a glass composition including about 59 to about 63 weight percent SiO2, about 13.7 to about 16 weight percent Al2O3, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, less than 1 weight percent TiO2, and RE2O3 present in an amount greater than 0 weight percent and less than 1.5 weight percent. In some embodiments, the composition may be substantially free of Li2O. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition may range up to about 22 to 24 weight percent. In some embodiments, the ratio of CaO to MgO (CaO) of the composition may range from about 22 to about 24 weight percent. The composition may further include up to 0.2 weight percent Na2O. In some cases, the composition may further include up to 0.2 weight percent K2O. In some cases, the composition may further include up to 0.2 weight percent Na2O. In some cases, the composition may further include up to 0.2 weight percent K2O.

[0056] In some embodiments, the one or more glass fibers may be formed from a glass composition comprising about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, less than 1 weight percent TiO2, less than 0.5 weight percent Li2O, and RE2O3 present in an amount greater than 0 weight percent and less than 1 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition may range from about 22 to 24 weight percent. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition may range from about 1.7 to about 2.0. In some embodiments, the composition may be substantially free of F2. In some embodiments, the composition may further comprise up to 0.2 weight percent Na2O. In some embodiments, the composition may further comprise up to 0.2 weight percent K2O.

[0057] In some embodiments, the one or more glass fibers can be formed from a glass composition that includes about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, less than 1 weight percent TiO2, and Li2O present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content can range from about 22 to 23 weight percent. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition can range from about 1.7 to about 2.0. In some embodiments, the composition can be substantially free of F2. In some embodiments, the composition can further include up to 0.2 weight percent Na2O. In some embodiments, the composition can further include up to 0.2 weight percent K2O.

[0058] In some embodiments, the one or more glass fibers may be formed from a glass composition including about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, less than 1 weight percent TiO2, and Li2O present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content may range from about 22 to about 24 weight percent. In some embodiments, the Young's modulus may be greater than 85 GPa. In some embodiments, the Young's modulus may be greater than 88 GPa. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition may range from about 1.7 to about 2.0. In some embodiments, the composition may be substantially free of F2. In some embodiments, the composition may further include up to 0.2 weight percent Na2O. Optionally, the composition may further comprise up to 0.2 weight percent KO.

[0059] In some embodiments, one or more glass fibers of the present invention can exhibit desirable mechanical and other properties. In some embodiments, the glass fibers of the present invention can exhibit one or more improved mechanical properties relative to glass fibers formed from E-glass. In some embodiments, the glass fibers of the present invention can provide one or more improved properties relative to glass fibers formed from R-glass and / or S-glass. Examples of desirable properties exhibited by some embodiments of the glass fibers of the present invention include: These include, but are not limited to, tensile strength, Young's modulus, coefficient of thermal expansion, softening point, elongation, and dielectric constant.

[0060] In some embodiments, one or more glass fibers can be formed from the glass compositions described herein. In certain embodiments, the glass fibers can have a desirable Young's modulus (E) value. In some cases, the glass fibers can have a Young's modulus of greater than about 85 GPa (e.g., greater than 87 GPa, greater than 88 GPa). For example, the Young's modulus is about 85 GPa, about 85.1 GPa, about 85.2 GPa, about 85.3 GPa, about 85.4 GPa, about 85.5 GPa, about 85.6 GPa, about 85.7 GPa, about 85.8 GPa, about 85.9 GPa, about 86 GPa, about 86.1 GPa, about 86.2 GPa, about 86.3 GPa, about 86.4 GPa, about 86.5 GPa, about 85.6 GPa, about 86.7 GPa, about 86.8 GPa, about 86.9 GPa, about 87 GPa, about 87.1 GPa, about 87.2 GPa, about The modulus may be 87.3 GPa, about 87.4 GPa, about 87.5 GPa, about 87.6 GPa, about 87.7 GPa, about 87.8 GPa, about 87.9 GPa, about 88 GPa, about 88.1 GPa, about 88.2 GPa, about 88.3 GPa, about 88.4 GPa, about 88.5 GPa, about 88.6 GPa, about 88.7 GPa, about 88.8 GPa, about 88.9 GPa, about 89 GPa, about 89.1 GPa, about 89.2 GPa, about 89.3 GPa, about 89.4 GPa, or about 89.5 GPa. In some embodiments, the glass fibers can have a Young's modulus of greater than about 90 GPa. In certain embodiments, the glass fibers can have a Young's modulus of up to 95 GPa.

[0061] In certain embodiments, the one or more glass fibers can have a desired density value. In some cases, the glass fibers can have a density value of about 2.7 g / cm 3 For example, the density can be about 2.55 g / cm 3 , about 2.56g / cm 3 , approx. 2.57g / cm 3 , about 2.58g / cm 3 , approx. 2.59g / cm 3 , about 2.6g / cm 3 , about 2.61g / cm 3, about 2.62g / cm 3 , about 2.63g / cm 3 , about 2.64g / cm 3 , about 2.65g / cm 3 , about 2.66g / cm 3 , approx. 2.67g / cm 3 , about 2.68g / cm 3 , approx. 2.69g / cm 3 , or about 2.7 g / cm 3 may be also possible.

[0062] The fiber glass strands can include glass fibers of various diameters depending on the desired application. In some embodiments, the fiber glass strands of the present invention can include at least one glass fiber having a diameter between about 5 and about 18 μm. In other embodiments, the at least one glass fiber has a diameter between about 5 and about 10 μm. In some embodiments, the fiber glass strands of the present invention can be formed into a roving. The roving can include assembled, multi-end, or single-end direct drawn rovings. The rovings comprising the fiber glass strands of the present invention can include direct drawn single-end rovings having various diameters and densities depending on the desired application. In some embodiments, the rovings comprising the fiber glass strands of the present invention exhibit a density of up to about 112 yd / lb. Some embodiments of the present invention relate to yarns comprising at least one fiber glass strand disclosed herein.

[0063] In some embodiments, the fiber glass strands can include a plurality of glass fibers of any one of the glass compositions described herein. For example, in some embodiments, the fiber glass strands can include a plurality of glass fibers formed from a glass composition including about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some cases, the composition can further include less than 0.5 weight percent Li2O. In some cases, Li2O can be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition can range from about 22 to 24 weight percent. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition can range from about 1.7 to about 2.0. In some cases, the composition can be substantially free of F2. In some cases, the composition can further include up to 0.2 weight percent Na2O. In some cases, the composition can further include up to 0.2 weight percent K2O. In some cases, RE2O3 can be present in the composition in an amount greater than 0 weight percent and less than 1 weight percent.

[0064] In other embodiments, the yarns of the present invention may include at least one fiber glass strand comprising one of the other glass compositions disclosed herein as part of the present invention.

[0065] In some embodiments, the yarn of the present invention can include at least one fiberglass strand as disclosed herein that is at least partially coated with a sizing composition. In some embodiments, the sizing composition can be compatible with a thermosetting polymer resin. In other embodiments, the sizing composition can include a starch-oil sizing composition.

[0066] The yarns can have a variety of linear mass densities depending on the desired application. In some embodiments, the yarns of the present invention can have a linear mass density of from about 5,000 yards / pound to about 10,000 yards / pound.

[0067] The yarns can have a variety of twist levels and directions depending on the desired application. In some embodiments, the yarns of the present invention can have a twist of about 0.5 to about 2 turns per inch in the z-direction. In other embodiments, the yarns of the present invention can have a twist of about 0.7 turns per inch in the z-direction.

[0068] The yarns can be made from one or more strands that are twisted together and / or plyed, depending on the desired application. The yarns can be made from one or more strands that are twisted together but not plyed, such yarns being known as "single yarns." The yarns of the present invention can be made from one or more strands that are twisted together but not plyed. In some embodiments, the yarns of the present invention can include 1-4 strands that are twisted together. In other embodiments, the yarns of the present invention can include one strand that is twisted.

[0069] In some embodiments, the fiber glass strands can include a plurality of glass fibers of any one of the glass compositions described herein. For example, in some embodiments, the fiber glass strands can include a plurality of glass fibers formed from a glass composition including about 59 to about 63 weight percent SiO2, about 13.7 to about 16 weight percent Al2O3, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some cases, the composition can further include less than 0.5 weight percent Li2O. In some cases, Li2O can be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition can range from about 22 to 24 weight percent. In some embodiments, the composition may have a ratio of CaO to MgO (CaO / MgO) ranging from about 1.6 to about 2.8. In some cases, the composition may be substantially free of F2. In some cases, the composition can further include up to 0.2 weight percent Na2O. In some cases, the composition can further include up to 0.2 weight percent K2O. In some cases, RE2O3 can be present in the composition in an amount greater than 0 weight percent and less than 1.5 weight percent.

[0070] In some embodiments, the roving can include a plurality of glass fibers of any one of the glass compositions described herein. For example, in some embodiments, the roving can include a plurality of glass fibers formed from a glass composition including about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some cases, the composition can further include less than 0.5 weight percent Li2O. In some cases, Li2O can be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition can range from about 22 to 24 weight percent. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition can range from about 1.7 to about 2.0. In some cases, the composition may be substantially free of F2. In some cases, the composition may further include up to 0.2 weight percent Na2O. In some cases, the composition may further include up to 0.2 weight percent K2O. In some cases, RE2O3 may be present in the composition in an amount greater than 0 weight percent and less than 1 weight percent.

[0071] In some embodiments, the yarn may include a plurality of glass fibers of any one of the glass compositions described herein. For example, in some embodiments, the yarn may include a plurality of glass fibers formed from a glass composition including about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition may be substantially free of Li2O. In some cases, the composition may further include less than 0.5 weight percent Li2O. In some cases, Li2O may be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition may range from about 22 to 24 weight percent. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition may range from about 1.7 to about 2.0. In some cases, the composition may be substantially free of F2. In some cases, the composition may further include up to 0.2 weight percent Na2O. In some cases, the composition may further include up to 0.2 weight percent K2O. In some cases, RE2O3 may be present in the composition in an amount greater than 0 weight percent and less than 1 weight percent.

[0072] Some embodiments of the present invention relate to a fabric comprising at least one fiberglass strand as disclosed herein. In some embodiments, the fabric may be woven. In other embodiments, the fabric may not be woven. In some embodiments, the fabric may comprise a plurality of glass fibers of any one of the glass compositions described herein. For example, in some embodiments, the fabric may comprise a plurality of glass fibers formed from a glass composition comprising about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition may comprise , may be substantially free of Li2O. In some embodiments, the composition may further include less than 0.5 weight percent Li2O. In some embodiments, Li2O may be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition may range from about 22 to 24 weight percent. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition may range from about 1.7 to about 2.0. In some embodiments, the composition may be substantially free of F2. In some embodiments, the composition may further include up to 0.2 weight percent Na2O. In some embodiments, the composition may further include up to 0.2 weight percent K2O. In some embodiments, RE2O3 may be present in the composition in an amount greater than 0 weight percent and less than 1 weight percent.

[0073] In some embodiments of the invention that include a fabric, the fiberglass fabric may be a fabric woven according to industrial fabric style no. 7781. In other embodiments, the fabric includes a plain weave, a twill, a houndstooth weave, a satin weave, a stitchbonded fabric (also known as a non-crimp fabric), or a "three-dimensional" woven fabric.

[0074] Some embodiments of the present invention relate to composites. In some embodiments, the polymer composite can include a plurality of glass fibers formed from a polymer material and a glass composition described herein. For example, in some embodiments, the polymer composite can include a plurality of glass fibers formed from a polymer material and a glass composition including about 59 to about 63 weight percent SiO2, about 13.7 to about 16 weight percent Al2O3, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some cases, the composition can further include less than 0.5 weight percent Li2O. In some cases, Li2O can be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition can range from about 22 to 24 weight percent. In some embodiments, the composition may have a ratio of CaO to MgO (CaO / MgO) in the range of about 1.7 to about 2.0. In some embodiments, the composition may be substantially free of F2. In some embodiments, the composition may further include up to 0.2 weight percent Na2O. In some embodiments, the composition may further include up to 0.2 weight percent K2O. In some embodiments, RE2O3 may be present in the composition in an amount greater than 0 weight percent and less than 1.5 weight percent. In some embodiments, the plurality of glass fibers may be in the form of a nonwoven fabric. In some embodiments, the plurality of glass fibers may be in the form of a woven fabric. In some embodiments, the polymeric material may include a thermoplastic polymer. In some embodiments, the polymeric material may include a thermosetting polymer.

[0075] In other embodiments, the composites of the present invention can include a polymer resin and a plurality of glass fibers deposited on the polymer resin, where at least one of the plurality of glass fibers is formed from one of the other glass compositions disclosed herein as part of the present invention. In some embodiments, the composites can include a polymer resin and at least one fiberglass strand as disclosed herein deposited on the polymer resin. In some embodiments, the composites can include at least a portion of a roving comprising a polymer resin and at least one fiberglass strand as disclosed herein deposited on the polymer resin. In other embodiments, the composites can include a polymer resin and at least one yarn as disclosed herein deposited on the polymer resin. In still other embodiments, the composites can include a polymer resin and at least one fabric as disclosed herein deposited on the polymer resin. In some embodiments, the composite can include at least one weft yarn comprising at least one fiberglass strand as disclosed herein, and at least one warp yarn comprising at least one fiberglass strand as disclosed herein.

[0076] The composites of the present invention can include a variety of polymer resins depending on the desired properties and applications. In some embodiments, the polymer resin can include an epoxy resin. In other embodiments, the polymer resin can include a polyethylene, polypropylene, polyamide, polyimide, polybutylene terephthalate, polycarbonate, thermoplastic polyurethane, phenolic resin, polyester, vinyl ester, polydicyclopentadiene, polyphenylene sulfide, polyether ether ketone, cyanate ester, bis-maleimide, or thermoset polyurethane resin.

[0077] In certain embodiments, an article of manufacture can include a plurality of glass fibers formed from any one of the glass compositions described herein. For example, in some embodiments, an article of manufacture can include a plurality of glass fibers formed from a glass composition comprising about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some cases, the composition can further comprise less than 0.5 weight percent Li2O. In some cases, Li2O can be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition can range from about 22 to 24 weight percent. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition can range from about 1.7 to about 2.0. In some cases, the composition may be substantially free of F2. In some cases, the composition may further include up to 0.2 weight percent Na2O. In some cases, the composition may further include up to 0.2 weight percent K2O. In some cases, RE2O3 may be present in the composition in an amount greater than 0 weight percent and less than 1 weight percent. In some embodiments, the plurality of glass fibers may be in the form of a nonwoven fabric. In some embodiments, the plurality of glass fibers may be in the form of a woven fabric.

[0078] In other embodiments, the article of manufacture can include a plurality of glass fibers formed from a polymeric material and a glass composition including about 59 to about 63 weight percent SiO2, about 13.7 to about 16.5 weight percent Al2O3, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some cases, the composition can further include less than 0.5 weight percent Li2O. In some cases, Li2O can be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition can range from about 22 to 24 weight percent. In some embodiments, the ratio of CaO to MgO (CaO / MgO) of the composition can range from about 1.7 to about 2.0. In some cases, the composition can be substantially free of F2. In some embodiments, the composition can further include up to 0.2 weight percent Na2O. In some embodiments, the composition can further include up to 0.2 weight percent K2O. In some embodiments, RE2O3 can be present in the composition in an amount greater than 0 weight percent and less than 1.5 weight percent. In some embodiments, the plurality of glass fibers can be in the form of a nonwoven fabric. In some embodiments, the plurality of glass fibers can be in the form of a woven fabric. In some embodiments, the polymeric material can include a thermoplastic polymer. In some embodiments, the polymeric material can include a thermoplastic polymer. It may include a curable polymer.

[0079] Some embodiments of the present invention relate to aerospace composites. In some embodiments, the aerospace composites can exhibit properties such as high strength, high elongation, high modulus, and / or low density that are desirable for use in aerospace applications. In some embodiments, the aerospace composites can include a plurality of glass fibers from a glass composition described herein. For example, in some embodiments, the aerospace composites can include a plurality of glass fibers formed from a polymeric material and a glass composition including about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some cases, the composition can further include less than 0.5 weight percent Li2O. In some cases, Li2O can be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition may range from about 22 to 24 weight percent. In some embodiments, the CaO to MgO ratio (CaO / MgO) of the composition may range from about 1.7 to about 2.0. In some embodiments, the composition may be substantially free of F2. In some embodiments, the composition may further include up to 0.2 weight percent Na2O. In some embodiments, the composition may further include up to 0.2 weight percent K2O. In some embodiments, RE2O3 may be present in the composition in an amount greater than 0 weight percent and less than 1 weight percent. In some embodiments, the plurality of glass fibers may be in the form of a nonwoven fabric. In some embodiments, the plurality of glass fibers may be in the form of a woven fabric. In some embodiments, the polymeric material may include a thermoplastic polymer. In some embodiments, the polymeric material may include a thermosetting polymer.

[0080] Examples of parts in which the composites of the present invention can be used include, but are not limited to, aerospace parts, such as floor panels, bins, galleys, seat backs, and other interior compartments potentially subject to impact, as well as exterior parts, such as helicopter rotor blades; automotive parts, such as structural parts, bodies, and bumpers; wind energy parts, such as wind turbine blades; high pressure vessels and / or tanks; safety and / or security applications; high mechanical stress applications; high energy impact applications, such as bulletproof or blast resistant applications; armor applications, such as the manufacture of armor panels; casings for missiles and other explosive delivery devices; applications in the oil and gas industry, other applications related to transportation and infrastructure, applications in alternative energy, high temperature insulation (i.e., heat shielding) applications (due to higher strength, higher modulus of elasticity, higher softening temperature, and higher glass transition temperature). In some embodiments, the composites can have a sheet-like physical dimension or shape and can be panels.

[0081] Some embodiments of the present invention relate to a prepreg. In some embodiments, the prepreg can include a plurality of glass fibers from the glass composition described herein. For example, in some embodiments, the prepreg can include a plurality of glass fibers formed from a polymeric material and a glass composition including about 60 to about 63 weight percent SiO2, about 14 to about 16 weight percent Al2O3, about 14 to about 16 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent Fe2O3, and less than 1 weight percent TiO2. In some embodiments, the composition can be substantially free of Li2O. In some cases, the composition can further include less than 0.5 weight percent Li2O. In some cases, Li2O can be present in an amount greater than 0 weight percent and less than 0.5 weight percent. In some embodiments, the (Li2O+MgO+Al2O3) content of the composition can range from about 22 to 24 weight percent. In some embodiments, the composition may have a ratio of CaO to MgO (CaO / MgO) in the range of about 1.7 to about 2.0. In some embodiments, the composition may be substantially free of F2. In some embodiments, the composition may further include up to 0.2 weight percent Na2O. In some embodiments, the composition may further include up to 0.2 weight percent K2O. In some embodiments, RE2O3 may be present in the composition in an amount greater than 0 weight percent and less than 1 weight percent. In some embodiments, the plurality of glass fibers may be in the form of a nonwoven fabric. In some embodiments, the plurality of glass fibers may be in the form of a woven fabric. In some embodiments, the polymeric material may include a thermoplastic polymer. In some embodiments, the polymeric material may include a thermosetting polymer.

[0082] While many of the applications for the glass fibers described herein are reinforcing applications, some embodiments of the glass fibers can be utilized in electronic applications, such as printed circuit boards ("PCBs").

[0083] More specifically, some embodiments relate to glass fiber reinforced materials that have electrical properties that enable enhanced performance of PCBs. For example, some embodiments can have a dielectric constant (Dk) that is desirable for electronics applications. The dielectric constant (Dk) of a material, also known as the "dielectric constant," is a measure of the material's ability to store electrical energy. Materials used as capacitors desirably have a relatively high Dk, while materials used as part of a PCB substrate desirably have a low Dk, especially for high speed circuits. Dk is the ratio of the charge that can be stored in a given material between two metal plates (i.e., capacitance) to the amount of charge that can be stored by the void (air or vacuum) between the same two metal plates. As another example, some embodiments can have a coefficient of thermal expansion that is desirable for electronics applications. Thus, some embodiments can be used in a variety of electrical applications, including, but not limited to, printed circuit boards, precursors to printed circuit boards (e.g., fabrics, laminates, prepregs, etc.). In such embodiments, a printed circuit board or other composite used in an electrical application can include a polymeric resin and a plurality of glass fibers in contact with the polymeric resin, where at least one of the plurality of glass fibers is formed from any of the glass compositions disclosed herein as part of the present invention. The polymeric resin can include any of the polymeric resins known to those of skill in the art for use in printed circuit boards or other electrical applications.

[0084] Turning now to the methods of making the glass fibers and related products of the present invention, the glass fibers of the present invention can be prepared in a conventional manner known in the art by blending the raw materials used to provide the specific oxides that form the fiber composition. The glass fibers according to various embodiments of the present invention can be formed using any method known in the art for forming glass fibers, and more desirably, any method known in the art for forming essentially continuous glass fibers. For example, the glass fibers according to non-limiting embodiments of the present invention can be formed using, but are not limited to, direct melt or indirect melt fiber forming methods. These methods are well known in the art and further discussion thereof is not believed to be necessary in light of the present disclosure. See, for example, KL Loewenstein, The Manufacturing Technology of Continuous Glass Fibers, 3 rd Ed., Elsevier, NY, 1993 at pages 47-48 and 117-234.

[0085] After the glass fibers are formed, the primary sizing composition can be applied to the glass fibers using any suitable method known to those skilled in the art. Those skilled in the art can select one of many commercially available sizing compositions for glass fibers based on several factors, including, for example, the performance characteristics of the sizing composition, the desired flexibility of the resulting fabric, cost, and other factors.

[0086] The fiberglass strands of the present invention can be prepared by any suitable method known to those skilled in the art. The fiberglass fabrics of the present invention can generally be made by any suitable method known to those skilled in the art, including, but not limited to, interlacing a weft yarn (also called a "fill yarn") with a plurality of warp yarns.

[0087] The composites of the present invention can be prepared by any suitable method known to those skilled in the art, including, but not limited to, vacuum assisted resin infusion molding, extrusion compounding, compression molding, resin transfer molding, filament winding, prepreg / autoclave curing, and pultrusion. The composites of the present invention can be prepared using such molding techniques as known to those skilled in the art. In particular, composite embodiments of the present invention incorporating woven fiberglass fabrics can be prepared using techniques known to those skilled in the art for preparing such composites.

[0088] The prepregs of the present invention can be prepared by any suitable means known to those skilled in the art, including, but not limited to, passing fiberglass strands, rovings, or fabrics through a resin bath, using a solvent-based resin, or using a resin film.

[0089] As previously mentioned, the composites of the present invention may include a polymer resin in some embodiments. A variety of polymer resins may be used. In some embodiments, polymer resins known to be useful for reinforcement applications may be particularly useful. In some embodiments, the polymer resin may include a thermosetting resin. Thermosetting resin systems useful in some embodiments of the present invention may include, but are not limited to, epoxy resin systems, phenol-based resins, polyesters, vinyl esters, thermosetting polyurethanes, polydicyclopentadiene (pDCPD) resins, cyanate esters, and bis-maleimides. In some embodiments, the polymer resin may include an epoxy resin. In other embodiments, the polymer resin may include a thermoplastic resin. Thermoplastic polymers useful in some embodiments of the present invention include, but are not limited to, polyethylene, polypropylene, polyamides (including nylons), polybutylene terephthalate, polycarbonate, thermoplastic polyurethanes (TPUs), polyphenylene sulfides, and polyetheretherketeone (PEEK). Commercially available thermosetting resins useful in some embodiments of the present invention may include, but are not limited to, polyethylene, polypropylene, polyamides (including nylons), polybutylene terephthalates, polycarbonates, thermoplastic polyurethanes (TPUs), polyphenylene sulfides, and polyetheretherketeone (PEEK). Non-limiting examples of commercially available polymer resins include Epikure MGS RIMH EPIKOTE Resin MGS® RIMR 135 epoxy with 1366 hardener (available from Momentive Specialty Chemicals Inc., Columbus, Ohio), Applied Polarmic MMFCS2 epoxy (available from Applied Poleramic, Inc., Benicia, Calif.), and EP255 modified epoxy (available from Barrday Composite Solutions, Millbury, Mass.).

[0090] The present invention is illustrated by the following series of specific embodiments, however, those skilled in the art will recognize that many other embodiments are also contemplated by the principles of the present invention. EXAMPLES

[0091] Table 1 provides data on several fiberizable glass compositions according to various embodiments of the invention, and various properties of such compositions. The glasses in these examples were made by melting a mixture of commercial and reagent grade chemicals in powder form (reagent grade chemicals were used only for the rare earth oxides) in 10% Rh / Pt crucibles at temperatures between 1500°C and 1550°C (2732°F and 2822°F) for four hours. Each batch was approximately 1000 grams. After the four hour melting period, the molten glass The glasses were poured onto a steel plate to quench the glass. Volatile species such as alkali oxides resulting from impurities in the ingredients used were not adjusted in the batches for diffusion losses due to their low concentration in the glasses. The compositions in the examples represent the as-batch compositions. Commercial ingredients were used in the preparation of the glasses. The batch calculations took into account the retention factors of the particular raw materials to calculate the oxides in each glass. The retention factors are based on the glass batch melting age and the oxide yield in the glass as measured. Therefore, the as-batch compositions illustrated in the examples are considered to be close to the measured compositions. Melting Properties

[0092] The melt viscosity and liquidus temperature as a function of temperature were measured according to ASTM Test Method C965 "Standard Practice for Measuring Viscosity of Glass Above the Softening Point," respectively. The temperature was determined using the "Standard Practice for Measurement of Liquidus Temperature of Glass by the Gradient Furnace Method" and C829 "Standard Practice for Measurement of Liquidus Temperature of Glass by the Gradient Furnace Method".

[0093] Table 1 shows the liquidus temperatures (T L ), the reference forming temperature (T F ) The difference between the formation temperature and the liquidus temperature (Delta T) is also shown. Mechanical properties

[0094] For certain glass compositions in Table 1, Young's modulus was also measured using the following technique. Approximately 50 grams of glass cullet having a composition corresponding to the appropriate example in Table 1 was remelted in a 90Pt / 10Rh crucible at a melting temperature defined by 100 poise for 2 hours. The crucible was then transferred to an electrically heated furnace, which was a vertical tube. The furnace temperature was preset to a fiber drawing temperature close to or equal to a melt viscosity of 1000 poise. The glass was allowed to equilibrate at that temperature for 1 hour before the fiber was drawn. The top of the fiber drawing furnace had a cover with a hole in the center, on which was mounted a water-cooled copper coil to regulate the cooling of the fiber. A silica rod was then manually dipped into the melt through the cooling coil, and a fiber approximately 1 to 1.5 m long was drawn and collected. The fiber diameter ranged from about 100 μm at one end to about 1000 μm at the other end. Table 1 [Table 1-1] Table 1, continued [Table 1-2] Table 1, continued [Table 1-3] Table 1, continued [Table 1-4] Table 1, continued [Table 1-5]

[0095] Desirable features that may be exhibited by various, but not necessarily all, embodiments of the present invention may include, but are not limited to, providing products such as fiberglass, fiberglass strands, fiberglass cloth, prepregs, and other products useful for reinforcement applications. Exemplary embodiments of suitable compositions, fibers, composites, and articles

[0096] As used hereinafter, any reference to a composition, composite, or article should be understood as a disjunctive reference to each of those compositions, composites, or articles (e.g., "Exemplary Embodiments 1-4 should be understood as Exemplary Embodiments 1, 2, 3, or 4").

[0097] Exemplary embodiment 1 is a glass composition suitable for fiber formation that includes about 60 to about 63 weight percent SiO, about 14 to about 16 weight percent AlO, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, and 0 to about 0.5 weight percent LiO, with a (LiO+MgO+AlO) content ranging up to about 22 to 24 weight percent.

[0098] Exemplary embodiment 2 is a composition of any exemplary embodiment described above or below that is substantially free of Li2O.

[0099] Exemplary embodiment 3 is any of the compositions of exemplary embodiments described above or below, wherein the ratio of CaO to MgO (CaO / MgO) ranges from about 1.7 to about 2.0.

[0100] Exemplary embodiment 4 is the composition of any exemplary embodiment described above or below, wherein the ratio of SiO2 to Al2O3 (SiO2 / Al2O3) ranges from about 3.5 to about 4.5.

[0101] Exemplary embodiment 5 is any of the compositions of exemplary embodiments described above or below, wherein the (Li2O+MgO+Al2O3) content ranges from about 22 to 23 weight percent.

[0102] Exemplary embodiment 6 is the composition of any exemplary embodiment described above or below, wherein the ratio of Al2O3 to (Al2O3+MgO+CaO), (Al2O3 / (Al2O3+MgO+CaO)), ranges from about 0.35 to about 0.45.

[0103] Exemplary embodiment 7 is the composition of any exemplary embodiment described above or below, which is substantially free of F2.

[0104] Exemplary embodiment 8 is the composition of any preceding or following exemplary embodiment, further comprising up to 0.2 weight percent Na2O.

[0105] Exemplary embodiment 9 is the composition of any preceding or following exemplary embodiment, further comprising up to 0.2 weight percent KO.

[0106] Exemplary embodiment 10 is a plurality of glass fibers formed from the glass composition of any of the exemplary embodiments described above or below.

[0107] Exemplary embodiment 11 is a plurality of glass fibers of any exemplary embodiment described above or below, wherein the glass fibers have an elastic modulus of greater than 85 GPa.

[0108] Exemplary embodiment 12 has a glass fiber of 2.7 g / cm 3 The plurality of glass fibers of any preceding or following exemplary embodiment having a density of less than 100 μm.

[0109] Exemplary embodiment 13 is a method for preparing a glass fiber having a forming temperature (T F ) of any exemplary embodiment described above or below.

[0110] Exemplary embodiment 14 is a glass fiber having a liquidus temperature (T L ) of any exemplary embodiment described above or below.

[0111] Exemplary embodiment 15 is a fiberglass strand comprising a plurality of glass fibers of any of the exemplary embodiments described above or below.

[0112] Exemplary embodiment 16 is a roving that includes a plurality of glass fibers of any of the exemplary embodiments described above or below.

[0113] Exemplary embodiment 17 is a yarn comprising a plurality of glass fibers of any of the exemplary embodiments described above or below.

[0114] Exemplary embodiment 18 is a woven fabric comprising a plurality of glass fibers of any of the exemplary embodiments described above or below.

[0115] Exemplary embodiment 19 is a nonwoven fabric comprising a plurality of glass fibers of any of the exemplary embodiments described above or below.

[0116] Exemplary embodiment 20 is a chopped glass strand that includes a plurality of glass fibers of any of the exemplary embodiments described above or below.

[0117] Exemplary embodiment 21 is a polymer composite including a polymer material and a plurality of glass fibers formed from the glass composition of any of the exemplary embodiments described above or below.

[0118] Exemplary embodiment 22 is a polymer composite of any exemplary embodiment described above or below, in which the plurality of glass fibers is in the form of a nonwoven fabric.

[0119] Exemplary embodiment 23 is a polymer composite of any exemplary embodiment described above or below, wherein the plurality of glass fibers is in the form of a woven fabric.

[0120] Exemplary embodiment 24 is a polymer composite of any exemplary embodiment described above or below in which the polymeric material comprises a thermoplastic polymer.

[0121] Exemplary embodiment 25 is a polymer composite of any exemplary embodiment described above or below, where the polymeric material comprises a thermosetting polymer.

[0122] Exemplary embodiment 26 is an article of manufacture that includes a plurality of glass fibers formed from the glass composition of any of the exemplary embodiments described above or below.

[0123] Exemplary embodiment 27 is a glass composition suitable for fiber formation comprising about 60 to about 63 weight percent SiO, about 14 to about 16 weight percent AlO, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, REO present in an amount greater than 0 weight percent and less than 1 weight percent, and substantially no LiO.

[0124] Exemplary embodiment 28 is a glass composition suitable for fiber formation comprising about 59 to about 63 weight percent SiO, about 13.7 to about 16 weight percent AlO, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, REO present in an amount greater than 0 weight percent and less than 1.5 weight percent, and substantially no LiO.

[0125] Exemplary embodiment 29 is the glass composition of any exemplary embodiment described above or below, wherein the ratio of SiO2 to Al2O3 (SiO2 / Al2O3) is in the range of about 3.6 to about 4.6.

[0126] Exemplary embodiment 30 is the glass composition of any exemplary embodiment described above or below, wherein the ratio of Al2O3 to (Al2O3+MgO+CaO), (Al2O3 / (Al2O3+MgO+CaO)), is in the range of about 0.33 to about 0.47.

[0127] Exemplary embodiment 31 is the glass composition of any exemplary embodiment described above or below, wherein the ratio of CaO to MgO (CaO / MgO) ranges from about 1.6 to about 2.8.

[0128] Exemplary embodiment 32 is a glass composition suitable for fiber formation comprising about 60 to about 63 weight percent SiO, about 14 to about 16 weight percent AlO, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, less than 0.5 weight percent LiO, REO present in an amount greater than 0 weight percent and less than 1 weight percent, and a (LiO+MgO+AlO) content ranging from about 22 to 24 weight percent. It is.

[0129] Exemplary embodiment 33 is a glass composition suitable for fiber formation comprising about 60 to about 63 weight percent SiO, about 14 to about 16 weight percent AlO, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, LiO is present in an amount greater than 0 weight percent and less than 0.5 weight percent, and the (LiO+MgO+AlO) content ranges up to about 22 to 23 weight percent.

[0130] Exemplary embodiment 34 is a plurality of glass fibers formed from a glass composition comprising about 60 to about 63 weight percent SiO, about 14 to about 16 weight percent AlO, about 14 to about 16.5 weight percent CaO, about 6 to about 8.5 weight percent MgO, less than 1 weight percent FeO, less than 1 weight percent TiO, LiO present in an amount greater than 0 weight percent and less than 0.5 weight percent, a (LiO+MgO+AlO) content ranging from about 22 to 24 weight percent, and a Young's modulus greater than 85 GPa.

[0131] Exemplary embodiment 35 is a plurality of glass fibers of any exemplary embodiment described above or below having a Young's modulus greater than 88 GPa.

[0132] Exemplary embodiment 36 is any of the foregoing exemplary embodiments, wherein the Al2O3 / (Al2O3+MgO+CaO) ratio ranges between 0.35 and 0.45.

[0133] Exemplary embodiment 37 is any of the previous exemplary embodiments wherein the Al2O3 / (Al2O3+MgO+CaO) ratio is less than 0.40.

[0134] Exemplary embodiment 38 is any of the foregoing exemplary embodiments wherein the Al2O3 / (Al2O3+MgO+CaO) ratio is in the range of 0.37 to 0.42.

[0135] Various embodiments of the present invention have been described herein. It should be recognized that these embodiments are merely illustrative of the present invention. Variations of these preferred embodiments may become apparent to those skilled in the art upon reading the foregoing description. The inventors expect that such variations will be utilized by those skilled in the art as appropriate, and contemplate that the present invention may be practiced in ways other than those specifically described herein. Accordingly, the present invention includes all modifications and equivalents of the subject matter recited in the claims appended hereto as permitted by applicable law. Moreover, any combination of the above-described elements is encompassed by the present invention in all possible variations thereof unless otherwise specified or otherwise clearly contradicted by context.

[0136] It should be understood that this description illustrates aspects of the present invention that are relevant for a clear understanding of the present invention. In order to simplify this description, certain aspects of the present invention that should be obvious to those skilled in the art and therefore may not facilitate a better understanding of the present invention are not presented. Although the present invention has been described in connection with certain embodiments, it is intended that the present invention is not limited to the disclosed specific embodiments, but encompasses modifications that are within the spirit and scope of the present invention.

[0137] According to a preferred embodiment of the present invention, for example, the following is provided: (Section 1) about 60 to about 63 weight percent SiO2; about 14 to about 16 weight percent Al2O3; about 14 to about 16.5 weight percent CaO; about 6 to about 8.5 weight percent MgO; Fe2O3 less than 1 weight percent, less than 1 weight percent TiO2, and About 0 to about 0.5 weight percent LiO 1. A glass composition suitable for fiber formation comprising: (Section 2) 2. The glass composition according to item 1, wherein the ratio of CaO to MgO (CaO / MgO) is in the range of about 1.7 to about 2.0. (Section 3) 3. The glass composition according to item 1 or 2, wherein the ratio of SiO2 to Al2O3 (SiO2 / Al2O3) is in the range of about 3.5 to about 4.5. (Section 4) 4. The glass composition according to any one of claims 1 to 3, wherein the (Li2O+MgO+Al2O3) content is in the range of about 22 to 23 weight percent. (Section 5) 5. The glass composition according to any one of items 1 to 4, wherein a ratio of Al2O3 to (Al2O3+MgO+CaO), (Al2O3 / (Al2O3+MgO+CaO)), is in the range of about 0.35 to about 0.45. (Section 6) 6. The glass composition according to any one of items 1 to 5, which is substantially free of F2. (Section 7) 7. The glass composition of any one of claims 1 to 6, further comprising up to 0.2 weight percent Na2O. (Section 8) 8. The glass composition of any one of claims 1 to 7, further comprising up to 0.2 weight percent KO. (Section 9) A plurality of glass fibers formed from the glass composition according to any one of items 1 to 8. (Item 10) 10. The glass fibers according to claim 9, having an elastic modulus of greater than 85 GPa. (Section 11) 2.7g / cm 3 11. The plurality of glass fibers according to claim 9 or 10, having a density of less than 10. (Section 12) Formation temperature (T F 12. The glass fibers according to any one of claims 9 to 11, having a thickness of 100 nm to 150 nm. (Section 13) Liquidus temperature (T L 13. The glass fibers according to any one of claims 9 to 12, having a thickness of 100 nm to 150 nm. (Section 14) 14. A fiber glass strand comprising a plurality of glass fibers according to any one of claims 9 to 13. (Section 15) 14. A roving comprising a plurality of glass fibers according to any one of claims 9 to 13. (Section 16) 14. A yarn comprising a plurality of glass fibers according to any one of claims 9 to 13. (Section 17) 14. A woven fabric comprising a plurality of glass fibers according to any one of items 9 to 13. (Section 18) 14. A nonwoven fabric comprising a plurality of glass fibers according to any one of items 9 to 13. (Section 19) 14. A chopped glass strand comprising a plurality of glass fibers according to any one of claims 9 to 13. (Section 20) a polymeric material, and A plurality of glass fibers formed from the glass composition according to any one of items 1 to 8. A polymer composite comprising: (Section 21) Item 22. The polymer composite material according to item 20, wherein the glass fibers are in the form of a nonwoven fabric. 21. The polymer composite of claim 20, wherein the plurality of glass fibers are in the form of a woven fabric. (Section 23) 23. The polymer composite of any one of claims 20 to 22, wherein the polymer material comprises a thermoplastic polymer. (Section 24) 23. The polymer composite of any one of claims 20 to 22, wherein the polymer material comprises a thermosetting polymer. (Section 25) 9. An article of manufacture comprising a plurality of glass fibers formed from the glass composition according to any one of claims 1 to 8. (Section 26) about 59 to about 63 weight percent SiO2; about 13.7 to about 16 weight percent Al2O3; about 14 to about 16.5 weight percent CaO; about 6 to about 8.5 weight percent MgO; Fe2O3 less than 1 weight percent, Less than 1 weight percent TiO2 A glass composition suitable for fiber formation comprising: RE2O3 is present in an amount greater than 0 weight percent and less than 1.5 weight percent; Substantially free of Li2O Glass composition. (Section 27) 27. The glass composition according to item 26, wherein the ratio of SiO2 to Al2O3 (SiO2 / Al2O3) is in the range of about 3.6 to about 4.6. (Section 28) 27. The glass composition according to item 26, wherein a ratio of Al2O3 to (Al2O3+MgO+CaO), (Al2O3 / (Al2O3+MgO+CaO)), is in the range of about 0.33 to about 0.47. (Section 29) 27. The glass composition according to item 26, wherein the ratio of CaO to MgO (CaO / MgO) is in the range of about 1.6 to about 2.8. (Section 30) about 60 to about 63 weight percent SiO2; about 14 to about 16 weight percent Al2O3; about 14 to about 16.5 weight percent CaO; about 6 to about 8.5 weight percent MgO; Fe2O3 less than 1 weight percent, less than 1 weight percent TiO2, Less than 0.5 weight percent LiO A glass composition suitable for fiber formation comprising: RE2O3 is present in an amount greater than 0 weight percent and less than 1 weight percent; The (Li2O+MgO+Al2O3) content ranges from about 22 to 24 weight percent. Glass composition. (Section 31) about 60 to about 63 weight percent SiO2; about 14 to about 16 weight percent Al2O3; about 14 to about 16.5 weight percent CaO; about 6 to about 8.5 weight percent MgO; Fe2O3 less than 1 weight percent, Less than 1 weight percent TiO2 A glass composition suitable for fiber formation comprising: LiO is present in an amount greater than 0 weight percent and less than 0.5 weight percent; The (Li2O+MgO+Al2O3) content ranges from about 22 to 23 weight percent. Glass composition. (Section 32) about 60 to about 63 weight percent SiO2; about 14 to about 16 weight percent Al2O3; about 14 to about 16.5 weight percent CaO; about 6 to about 8.5 weight percent MgO; Fe2O3 less than 1 weight percent, Less than 1 weight percent TiO2 A plurality of glass fibers, comprising: LiO is present in an amount greater than 0 weight percent and less than 0.5 weight percent; (Li2O+MgO+Al2O3) content in the range of about 22-24 weight percent and a Young's modulus of greater than 85 GPa; Multiple glass fibers. (Section 33) 33. The glass fibers according to claim 32, wherein the Young's modulus is greater than 88 GPa.

Claims

[Claim 1] Desirable mechanical properties.